The role of accent and ethnicity in the professional and academic context - Chan, Swee Heng; Abdullah, Ain Nadzimah; Thamer Ahmed, Zainab (Australian International Academic Centre, 2013)
Language learning may be affected by a language instructor’s accent. Many studies have been carried out to investigate whether accent has an influence on learners’ perceptions toward their instructors or whether accent can affect employability. This overview links studies on accents through an empirical literature review on native and non-native accents, summarizing the most significant studies conducted to investigate learners’ attitude toward accents. The learners as participants are both non-native and native speakers of a language. The results of the review demonstrated that speakers who use the standard language are preferred for prestigious jobs, whereas the nonstandard accented speakers are preferred for low-status jobs. Moreover, British and American accents are the most preferred by learners of English. Thus, the learners tended to show positive attitudes toward American and British accents and also adopt these varieties as models of pronunciation for their learning of English. In this review, limitations of some studies are highlighted and some implications for future studies related to accents, language learning at tertiary level and employability are discussed.